Cerita Rakyat Pulau Samosir "Asal Usul Danau Toba" - Halimatussakdiah Nst; Rindang Nur Rezeki Sitorus; Sri Sintya Lovyanda; Ummi Ifroh; Widya Ramadhani; Zahwa Nirwana Dwi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Basically, in a text, a title is usually written at the very top or middle of the text without punctuation. However, there are text titles that are written accompanied by punctuation. Then the title is also sometimes placed below the top title or rubric title. Phenomena like this show that para-text analysis is also important in carrying out discourse analysis. On this basis, the author is interested in conducting research on narrative texts both in terms of para-text, schematics, context, and the realization of actions and reactions of discourse in the narrative genre, which in this case is a folklore text originating from the Toba people of North Sumatra. By conducting a comprehensive study, researchers can help students' understanding of discourse analysis with the theory of Functional Systemic Linguistics, but also advance Indonesian literary works through the use of data sources from the folklore origin of "Lake Toba".